Pengaruh Harga Paket Internet dan Kualitas Layanan Terhadap Loyalitas Pelanggan - Riezka Putri Imanda; Halimah Zahrah (Indonesia Economic Journal, 2026)
The widespread increase in internet usage has driven progress in the telecommunications sector, especially among internet service providers. Price and service quality are important factors influencing customer loyalty. This study aims to analyze the effect of price and service quality on customer loyalty at R and R Cell Terusan Buah Batu. This study uses a quantitative approach with descriptive and verification methods. The research sample was obtained using the Accidental Sampling technique. Data were collected using a questionnaire with a Likert scale of 1-5 that has been tested for validity and reliability. The data analysis technique used multiple linear regression analysis with the help of SPSS version 25. The results of the study indicate that price has no positive and insignificant effect on customer loyalty. Service quality has a positive and significant effect on customer loyalty. Price and service quality simultaneously have a significant effect on customer loyalty. Service quality has a more dominant influence than price. It can be concluded that the combination of price and service quality has a substantial impact on customer loyalty. Suggestions in this study can formulate more effective marketing strategies based on an understanding of the factors that influence customer loyalty.